(untitled) (International Journal of Engineering and Computer Science, 2015)
In recent years, Wireless Sensor Network (WSN) finds applicability in every domain namely the military, health care, structure monitoring, forest surveillance, agriculture, etc, as they can be deployed in unattended hostile environment. WSN will be an integral part of human lives. However one of the main concerns in WSN is its limited resources. Wireless sensor networks consist of one or more base stations and a number of sensor nodes that get stimulated from external events. This paper provides message authentication scheme in wireless sensor networks. Message authentication is the effective ways to prohibited unauthorized users and unwanted messages forwarded in wireless sensor networks. Many message authentication methods have been developed, based on either public-key or symmetric key cryptosystems. But most of them have the lack of scalability, limitations of high computational and communication overhead, resilience to node compromise attacks and threshold problem. To solve such problem, a new authentication scheme has been developed using the elliptic curve cryptography. This scheme proposes any node can transmit any number of messages without threshold problem and also provide message source privacy.